A late summer survey of Britain's wildfowl - Salmon, D G (Wildfowl, 1988)
A Late Summer Wildfowl Survey was organised in 1985, as an extension of the regular monthly National Wildfowl Counts to late July and August. Over 1,000 localities were covered. Many important moulting, post-breeding and early autumn passage resorts were identified, and in some cases re-assessments of previous estimates of the late summer populations were possible. Recommendations are made as to methodology for future surveys, and the possible application of the results to criteria for national importance.